The determinants of enterprise profi tability during reduced economic activity - Steinerowska-Streb, Izabella (Journal of Business Economics and Management, 2012)
The aim of this study was to identify the characteristic features of small and medium enterprises (SMEs) which contribute to the decrease of profits of those SMEs during a period of reduced economic activity. The investigation was based on a sample of 1107 SMEs functioning in the Polish market. The empirical evidence found the type of manager, market range and legal form as determining factors of SME profits during a period of reduced economic activity. The received results led to the development of a model of firm-specific variables that resul in the decrease of SMEs profits through an economic slowdown.